Monitoramento e modelagem hidrológica sub-horária no bioma Pampa: nanobacia na estação experimental na UFSM - Silva, Milene Priebe e (2020)
Knowing the hydrological cycle is essential to understand the changes resulting from changes in land use and also to assist in better management of water resources. These studies are usually carried out on a basin scale, and can be subdivided into sub-basins or microbasins, which allow to more easily characterize and identify the place of interest. In this work, the term nanobasin was adopted, to differentiate the study area, of only 5,88 ha. Thus, the main objective of this work was to contribute to the generation of data on the hydrological dimension of ecosystem services in the native grassland under extensive livestock, through the instrumentation of a basin in the Pampa Biome, and to use the monitoring data in the SWAT model. The methodology was carried out in stages, the first being obtaining the data for insertion in the SWAT database, through the instrumentation of the nanobasin and selecting the events. Subsequently, sensitivity, calibration and validation analyzes were performed, and finally, graphic and statistical analyzes were performed. The results are presented in the form of a technical note and an article, the first addressing the difficulties encountered during monitoring, such as negative levels, obstruction and overflow of the flow-measuring structure, a fact that made it difficult to obtain a continuous series of data; and the article discussing the hydrological behavior in the nanobasin and the test results using SWAT with event calibration. For the article, 10 rain events were selected, 5 for calibration and 5 for validation. In the calibration, 3 events demonstrated satisfactory results, but in the validation the results were unsatisfactory, possibly because there is no information on the previous conditions of soil moisture and because the SWAT is a continuous model. Even so, the selected events characterized the hydrological behavior in the nanobasin very well, showing periods of minimum and maximum flows, in addition to their intermittent behavior. this area of native grassland is strongly influenced by lateral flow, a fact that may be related to the textural horizon B of the study area. It is suggested to continue monitoring, which will allow new tests to be carried out, and more work can be developed seeking to support the decision-making process regarding management policies in the Pampa Biome and assist in discussions regarding water availability in basins as small.